The Factors influencing entrepreneurial intentions amongst sport management students - Zwane, Bonginkosi Siyethemba (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
ABSTRACT Background Given the size of the sports industry in relation to the global economy, more research is focusing on how to identify entrepreneurial opportunities in sports. Purpose This study aimed to investigate the factors influencing entrepreneurial intentions amongst sport management students at a South African university. Method Structured interviews were used to gather information from 10 undergraduate sport management students for the qualitative, explanatory study. Using ATLAS.ti and thematic analyses, the collected data were examined. Results The following themes emerged from the study; namely, personality traits, attitudes towards entrepreneurship, entrepreneurial self-efficacy, perceived university support, perceived structural support, and subjective norms. The results of this study indicate that sport management students have a favourable attitude towards entrepreneurship, which is influenced by their family and friends - and by their own sense of their own ability to succeed in business. Conclusion Universities should consider incorporating entrepreneurship into their sport management curriculum design and teaching methods to enhance students' entrepreneurial mindset and self-efficacy. Contribution This study contributes to the discussion around developing attitudes and intentions toward entrepreneurship as a livelihood option for sport management students. Keywords: entrepreneurial intention, sport management, sport entrepreneurship